Substantiation of the design features of the working body of the centrifugal mineral fertilizer spreader - Пономаренко, Наталія Олександрівна; Кобець, Анатолій Степанович; Науменко, Микола Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
Mineral fertilizer distributors do not meet the agrotechnical requirements to the process. Therefore, it was decided to develop a centrifugal working body for machines that apply fertilizers, which would ensure application uniformity of 90%. The problems of increasing the efficiency of mechanical application of solid mineral fertilizers by improving the quality of their distribution on the soil surface and increasing the machine performance were solved in the paper. Substantiation of the process parameters of centrifugal mineral fertilizer distributors was developed. One of the possible causes of the nonuniform distribution of fertilizers by centrifugal spreaders was found out. Patterns of descent of fertilizers from the distributing bodies and the nature of their distribution on the soil surface were determined. The main factors that have a decisive influence on the machine performance were defined. Formulas, simplified enough for engineering application that allow to substantiate a design of disk fertilizer spreader that guarantees improved spreading were derived. Technical measures, introduced in mass production were developed.